Type a math problem

This site uses cookies for analytics, personalized content and ads. By continuing to browse this site, you agree to this use. Learn more

Type a math problem

Solve for K

K=\frac{4q}{9}

$K=94q $

Steps for Solving Linear Equation

q = \frac { K ( 2 ) ( 3 ) ^ { 2 } } { 8 }

$q=8K(2)(3)_{2} $

Calculate 3 to the power of 2 and get 9.

Calculate $3$ to the power of $2$ and get $9$.

q=\frac{K\times 2\times 9}{8}

$q=8K×2×9 $

Multiply 2 and 9 to get 18.

Multiply $2$ and $9$ to get $18$.

q=\frac{K\times 18}{8}

$q=8K×18 $

Divide K\times 18 by 8 to get K\times \left(\frac{9}{4}\right).

Divide $K×18$ by $8$ to get $K×(49 )$.

q=K\times \left(\frac{9}{4}\right)

$q=K×(49 )$

Swap sides so that all variable terms are on the left hand side.

Swap sides so that all variable terms are on the left hand side.

K\times \left(\frac{9}{4}\right)=q

$K×(49 )=q$

The equation is in standard form.

The equation is in standard form.

\frac{9}{4}K=q

$49 K=q$

Divide both sides of the equation by \frac{9}{4}=2.25, which is the same as multiplying both sides by the reciprocal of the fraction.

Divide both sides of the equation by $49 =2.25$, which is the same as multiplying both sides by the reciprocal of the fraction.

\frac{\frac{9}{4}K}{\frac{9}{4}}=\frac{q}{\frac{9}{4}}

$49 49 K =49 q $

Dividing by \frac{9}{4}=2.25 undoes the multiplication by \frac{9}{4}=2.25.

Dividing by $49 =2.25$ undoes the multiplication by $49 =2.25$.

K=\frac{q}{\frac{9}{4}}

$K=49 q $

Divide q by \frac{9}{4}=2.25 by multiplying q by the reciprocal of \frac{9}{4}=2.25.

Divide $q$ by $49 =2.25$ by multiplying $q$ by the reciprocal of $49 =2.25$.

K=\frac{4q}{9}

$K=94q $

Solve for q

q=\frac{9K}{4}

$q=49K $

Solution Steps

q = \frac { K ( 2 ) ( 3 ) ^ { 2 } } { 8 }

$q=8K(2)(3)_{2} $

Calculate 3 to the power of 2 and get 9.

Calculate $3$ to the power of $2$ and get $9$.

q=\frac{K\times 2\times 9}{8}

$q=8K×2×9 $

Multiply 2 and 9 to get 18.

Multiply $2$ and $9$ to get $18$.

q=\frac{K\times 18}{8}

$q=8K×18 $

Divide K\times 18 by 8 to get K\times \left(\frac{9}{4}\right).

Divide $K×18$ by $8$ to get $K×(49 )$.

q=K\times \left(\frac{9}{4}\right)

$q=K×(49 )$

Assign q

q≔\frac{9K}{4}

$q:=49K $

Quiz

Linear Equation

10 problems similar to:

q = \frac { K ( 2 ) ( 3 ) ^ { 2 } } { 8 }

$q=8K(2)(3)_{2} $

Giving is as easy as 1, 2, 3

Get 1,000 points to donate to a school of your choice when you join Give With Bing

Share

Copy

Copied to clipboard

q=\frac{K\times 2\times 9}{8}

Calculate 3 to the power of 2 and get 9.

q=\frac{K\times 18}{8}

Multiply 2 and 9 to get 18.

q=K\times \left(\frac{9}{4}\right)

Divide K\times 18 by 8 to get K\times \left(\frac{9}{4}\right).

K\times \left(\frac{9}{4}\right)=q

Swap sides so that all variable terms are on the left hand side.

\frac{9}{4}K=q

The equation is in standard form.

\frac{\frac{9}{4}K}{\frac{9}{4}}=\frac{q}{\frac{9}{4}}

Divide both sides of the equation by \frac{9}{4}=2.25, which is the same as multiplying both sides by the reciprocal of the fraction.

K=\frac{q}{\frac{9}{4}}

Dividing by \frac{9}{4}=2.25 undoes the multiplication by \frac{9}{4}=2.25.

K=\frac{4q}{9}

Divide q by \frac{9}{4}=2.25 by multiplying q by the reciprocal of \frac{9}{4}=2.25.

q=\frac{K\times 2\times 9}{8}

Calculate 3 to the power of 2 and get 9.

q=\frac{K\times 18}{8}

Multiply 2 and 9 to get 18.

q=K\times \left(\frac{9}{4}\right)

Divide K\times 18 by 8 to get K\times \left(\frac{9}{4}\right).

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { - 1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $

Back to top